The Role of Fecal Microbiota Transplantation in Modulating the Gut Microbiota-Testis Axis for Male Infertility Treatment - Langgeng Agung Waskito; Nadda Kalila (Indonesian Andrology and Biomedical Journal, 2026)
Background : Infertility has become a global health issues as it is reported of 10 – 15% of couple worldwide. Male factor are found to be mainly responsible for 20-30% of infertility cases and contribute to overall cases of 50%, caused by abnormality of motile and functional sperm. Gut dysbiosis or disrupted gut microbiota held one of the to play a role in male infertility. Research now is conducted on the use of fecal microbiota transplantation to improve the gut microbiota. Reviews : This literature review are being researched from Pubmed, EBSCO, Proquest, Cochrane Library, and ScienceDirect. There are 4 types of studies included in this review, focusing on in-vivo, in-vitro, pre-clinical, and clinical research within the year 2019 -2024. We are also focusing on the study that discusses the concept of fecal microbiota transplantations, male infertility treatment, related to the gut microbiota testis axis. Summary : In conclusion, fecal microbiota transplantations specifically imporved FMT indicates a pledge as a treatment for improving male infertility. Further study is vindicated to ascertain these intervention and to learn the advanced mechnism underlying the impact of FMT on modulating the gut microbiota testis axis.